2018
DOI: 10.3390/ma11081410
|View full text |Cite
|
Sign up to set email alerts
|

Calcined Mussel Shell Powder (CMSP) via Modification with Surfactants: Application for Antistatic Oil-Removal

Abstract: Biomass is known to efficiently adsorb pollutants from wastewater. In this paper, we demonstrated that a new antistatic oil-cleaning material can be prepared and assembled by using two surfactants, alkyl polyglucosides (APG) and dimethyl octadecyl hydroxy ethyl ammonium nitrate (SN), to modify calcined mussel shell powder (CMSP) through a two-step hydrotherm-assisted adsorption. The pore size and structure of CMSP was measured by BET and a contact angle meter was used to characterize the surface wetting abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The surface area, pore volume and pore diameter of lala clam shell were measured as 2.09 m 2 /g, 0.16 cm 3 /g and 0.15 nm, respectively. The surface area of lala clam shell is relatively comparable to the values of several other shells reported previously by Wei et al (2018) for Mytilus edulis mussel shell (1.120 m 2 /g), Tsai (2013) for Crassostrea gigas Pacific oyster shell (4.05 m 2 /g) and de Paiva, Fraga, Sales, Carvalho, and Sobrinho (2018) for Anomalocardia brasiliana clam shell (4.44 m 2 /g). According to the IUPAC, the porosity of substances can be grouped into three different classes of diameter groups (d), namely micropores (d < 2 nm), mesopores…”
Section: Resultssupporting
confidence: 85%
“…The surface area, pore volume and pore diameter of lala clam shell were measured as 2.09 m 2 /g, 0.16 cm 3 /g and 0.15 nm, respectively. The surface area of lala clam shell is relatively comparable to the values of several other shells reported previously by Wei et al (2018) for Mytilus edulis mussel shell (1.120 m 2 /g), Tsai (2013) for Crassostrea gigas Pacific oyster shell (4.05 m 2 /g) and de Paiva, Fraga, Sales, Carvalho, and Sobrinho (2018) for Anomalocardia brasiliana clam shell (4.44 m 2 /g). According to the IUPAC, the porosity of substances can be grouped into three different classes of diameter groups (d), namely micropores (d < 2 nm), mesopores…”
Section: Resultssupporting
confidence: 85%
“…[29][30][31]66,67 However, following harvest of esh 65 and/or pearl 66,67 the shells are discarded as waste, which bears huge prospect as a biological material. [32][33][34][35][36][37][38] While discarded marine shells derived from mussels, oysters, clams and abalones have been characterized as biological material with multiple utility, few efforts have been made from the freshwater mussels. 41,54 Several studies have shown that shells of marine bivalves and gastropods are more worthy as waste with multiple applications in the eld of biodiesel production, 39,40 waste water treatment, 46,47 soil amelioration, [48][49][50] biosorbent for dye and heavy metal, 45,51,52,54,55 llers and alternative to mortars, 56,57 and as an alternative to the bone materials.…”
Section: Discussionmentioning
confidence: 99%
“…The waste shells are highly valued resource used in multiple purposes. [32][33][34][35][36] Owing to a rich source of calcium carbonate, the shells of mussels are converted into useful lime, 37 which can facilitate oil removal 38 or act as a catalyst in biodiesel formation 39,40 or as a catalyst in the 4H pyran formation. 41 The mussel shells can be incorporated in polypropylene 42 or in reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the adsorption process to treat oily wastewater effluents with activated carbon is a promising alternative treatment method that is scarcely explored [12]. In general, activated carbons are the most widely used adsorbents in both granular and powdered forms due to their excellent adsorption capability for organic matter, which is usually related to their porosity, specific surface area, and pore volume [13,14,15]. For example, the adsorption performance of methylene blue onto activated carbon prepared from date pits has been explored [16].…”
Section: Introductionmentioning
confidence: 99%